PROPOSED CONTENT MARKETING STRATEGY FOR LIFESTYLE COMPANY: CASE OF ARETE INC. - Agustiar, Gilang
As the market continues to evolve, traditional marketing techniques are slowly getting replaced by digital marketing. From all techniques of digital marketing, content marketing is one of the most popular techniques in the last three years. However, many new businesses have difficulties to develop and execute their own content marketing strategy in regards of limited knowledge of the content marketing. As a newly launched business, Arete Inc. is a company that are focusing on providing the best product to help people maximize their potential. The first product is called Productivity Journal. Based on the current sales data, from 61 products sold, there are only 4 products sold through online channel. After gaining feedback from the target market, some of the issues that arises are the content is not effectively explaining the value of the product and lack of consistency to update. Both issues are related to the ineffectiveness of the current content marketing. To solve the problem, the researcher decided to focus on developing the content marketing strategy because it could improve the brand awareness and the online sales performance in the long run. In this study, the researcher conducts semi-structured interviews to 20 people from current target market. The researcher also conducts desk research by online observation to create a content benchmark to competitors. The result of the data collection will be developed into the content marketing strategy for Arete Inc. The final outcomes will be six documents: the business case, the buyer persona, the relevant digital content, the buyer journey map, the channel plan, and the global editorial calendar. As the result of the study, there are four buyer personas developed includes college student, entrepreneur, freelancer, and startup worker. Each persona has several similar characteristics including have their own goal, interested in personal development, and learning about their career in social media. The relevant digital content includes content as a problem solver being the most relevant characteristics. Videos and infographics being the most relevant format. Relaxed but insightful as the most relevant content style. The most common social media used by the persona are Facebook, Instagram, Line, and Youtube.